Synthesis of CdS QDs with single cubic and hexagonal lattice for blue-light-blocking nanocomposite films with a narrow absorbing transitional band. (September 2020) - Li, Xinxin; Xu, Jinku
Graphical abstract: Abstract: It is highly expected to develop blue-light-blocking filters with narrow absorbing transitional band, so as to filter out only harmful blue light below 455 nm. In this paper, CdS quantum dots (QDs) with single cubic and hexagonal lattice were synthesized by a solvothermal method using mercaptoethanol as capping agent. The results show that hexagonal-type CdS QDs with a diameter about 2.5 nm was synthesized after 10 min of reaction, and then grow slowly up at low temperature (80 °C). Higher temperature (160 °C) helps to synthesize cubic-type CdS that grows rapidly to a final size about 4 nm. Hexagonal and cubic CdS all show separated energy level structure corresponding to a band gap of 3.59 eV and 3.1 eV, respectively. CdS QDs were compounded into poly( N, N -dimethacrylamide) matrices to prepare transparent nanocomposite films, in which the optical properties of CdS QDs can be preserved, and the nanocomposite films, especially ones with 30 wt% of cubic CdS, shows a narrow blue-light-absorbing transitional band. The wavelength span from 5 % to 80 % of maximum transmittance is only 20 nm (440−460 nm), indicating a potential application in ocular protection by sealing it between two layers of glass panels as blue-light-blocking filter due to its sharp cut on/off and wavelength-dependent blue transmittance.